An Overview of Wireless Charging Systems for Electric Vehicles: From Historical Evolution to Modern Applications - Liu, Ruoning; Xu, Zhanguo; Chen, Jiangchuan; Wang, Yun (IEEE International Conference on Industrial Technology (Online), 2025)
Wireless charging systems have emerged as a convenient and efficient solution for powering electronic devices and electric vehicles without the requirement for physical connectors, gaining significant attention in recent years. This paper reviews the current development of wireless charging technology, including its background, main classifications, and common charging methods, such as inductive power transfer and coupled magnetic resonance. Newer approaches, key challenges impacting power transmission efficiency, and corresponding mitigation strategies are also examined. Safety considerations and environmental impacts are evaluated to understand their influence on technology adoption. Finally, future trends and research priorities are outlined, proposing innovations needed to address current limitations and enhance wireless power transmission capabilities. This review aims to provide a comprehensive overview of wireless charging systems, aiding researchers and practitioners in understanding recent advancements and contributing to the development of next-generation solutions.